The garden tomb of Humayun : an abode in paradise - Misra, Neeru, 1957-; Misra, Tanay (New Delhi : Aryan Books International : Advertising & Communication Support, 2003)
History of the tomb of Humayun, Emperor of Hindustan, 1508-1556, in Delhi; pictorial presentation.
Includes bibliographical references (p. 157-164) and index.
Keywords: Humayun, -- Emperor of Hindustan, -- 1508-1556 -- Tomb; Humayun, -- Emperor of Hindustan, -- 1508-1556 -- Tomb -- Pictorial works; Tombs -- India -- Delhi; Tombs -- India -- Delhi -- Pictorial works; Gardens, Mogul -- India -- Delhi; Gardens, Mogul -- India -- Delhi -- Pictorial works; India -- Kings and rulers -- Tombs; India -- Kings and rulers -- Tombs -- Pictorial works; Delhi (India) -- Antiquities